2010
DOI: 10.1183/09031936.00146510
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of matrix metalloproteinases: a critical balance

Abstract: Matrix metalloproteinases (MMPs) are members of the metzincin group of proteases which share the conserved zinc-binding motif in their catalytic active site. It was originally thought that their main function is to degrade the various components of the extracellular matrix (ECM), yet recent studies have led us to appreciate their significance as regulators of extracellular tissue signalling networks. Due to the broad spectrum of their substrate specificity, MMPs contribute to the homeostasis of many tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
398
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(418 citation statements)
references
References 121 publications
10
398
0
10
Order By: Relevance
“…ECM degradation is necessary for cellular migration and is carried out by MMPs and other proteases. In recent years, new studies have also shown that MMPs play a role in regulating extracellular tissue signaling networks [24]. Due to their destructive nature, the activity of these ECM proteases have to be controlled.…”
Section: Resultsmentioning
confidence: 99%
“…ECM degradation is necessary for cellular migration and is carried out by MMPs and other proteases. In recent years, new studies have also shown that MMPs play a role in regulating extracellular tissue signaling networks [24]. Due to their destructive nature, the activity of these ECM proteases have to be controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Since the early work on cloning and identifying MMPs (and their Metzincin relatives), we've uncovered many questions regarding their regulation at the gene and post-translational levels (47)(48)(49) (Fig. 7).…”
Section: Outlook For the Future: Looking Down The Trackmentioning
confidence: 99%
“…Cystatins are structurally conserved, low molecular weight endogenous cysteine protease inhibitors found in most body compartments and fluids. Characteristically, they are described to function intra-and/or extracellularly to inhibit their target cysteine enzymes (for example, cathepsins) to maintain a crucial protease-inhibitor balance, thus regulating damaging proteolytic activities (2,3). Distinct cystatins regulate specific cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%